WOMEN IN THE LOCAL POLITICAL VORTEX: A STUDY OF WOMEN CANDIDATES INVOLVEMENT IN 2020 REGIONAL ELECTIONS IN TANAH DATAR - Budiman, Novi (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to describe the candidacy process and challenges of female candidates in the 2020 regional elections in Tanah Datar Regency as well as campaign issues promoted by female candidates based on gender perspective. This research is a qualitative research using candidacy theory. The findings of this study that the challenge faced by Betty Shadiq Pasadigue in the contestation of the 2020 Regional Elections of Tanah Datar Regency is the emergence of gender stereotypes and negative views of women's leadership as regional leader, although the LKAAM of Tanah Datar Regency has affirmed that women's leadership in the political field is permitted.